2021
DOI: 10.3390/ijms222212454
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Plant Hormones in the Interaction of Colletotrichum Species with Their Host Plants

Abstract: Colletotrichum is a plant pathogenic fungus which is able to infect virtually every economically important plant species. Up to now no common infection mechanism has been identified comparing different plant and Colletotrichum species. Plant hormones play a crucial role in plant-pathogen interactions regardless whether they are symbiotic or pathogenic. In this review we analyze the role of ethylene, abscisic acid, jasmonic acid, auxin and salicylic acid during Colletotrichum infections. Different Colletotrichu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 111 publications
(117 reference statements)
1
8
0
Order By: Relevance
“…Auxin also plays an important role in plant–microbe interactions, including interactions between plant hosts and pathogenic microorganisms, which cause disease ( Kunkel and Johnson, 2021 ). In general, indole-3-acetate (IAA) can act both as a plant hormone that modulates host signaling and physiology to increase host susceptibility and as a microbial signal that directly impacts the pathogen by producing virulence ( Svoboda et al., 2021 ). A previous study has revealed that IAA biosynthesis may participate in the tea plant– C. camelliae interaction ( Lu et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Auxin also plays an important role in plant–microbe interactions, including interactions between plant hosts and pathogenic microorganisms, which cause disease ( Kunkel and Johnson, 2021 ). In general, indole-3-acetate (IAA) can act both as a plant hormone that modulates host signaling and physiology to increase host susceptibility and as a microbial signal that directly impacts the pathogen by producing virulence ( Svoboda et al., 2021 ). A previous study has revealed that IAA biosynthesis may participate in the tea plant– C. camelliae interaction ( Lu et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most DEGs of ethylene-responsive factors were upregulated in the double inoculation of AMF and C. camelliae , possibly implying that the transcription factors were one of the key pathways to resist the pathogen after AMF inoculation. Ethylene-responsive factors are excellent candidates for developing plant resistance to anthracnose and other fungal diseases ( Svoboda et al., 2021 ), and loss of ERF114 function caused impaired disease resistance ( Li et al., 2022 ). Therefore, future research could be focused on this field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auxin is a group of molecules (including IAA) that not only acts as a growth hormone mediating apical growth and development but also plays a central role in balancing plant resistance responses ( Denancé et al, 2013 ), which could negatively impact plant defense by suppressing SA levels and signaling ( Robert-Seilaniantz et al, 2011 ; Pieterse et al, 2012 ; Svoboda et al, 2021 ). Some fungal pathogens, e.g., Fusarium oxysporum , F. arthosporioides , and C. gloeosporioides f. sp.…”
Section: Discussionmentioning
confidence: 99%
“…Hormone signaling was already reported to be involved in plant defense responses to Colletotrichum spp. (Svoboda et al, 2021). Our study revealed time-specific genes modulated in the MRP, related to Ca 2+ fluctuations, ROS, and hormone signaling, indicating that these signaling events have a strong correlation with soybean defense mechanisms against C. truncatum (Figure 4).…”
Section: Discussionmentioning
confidence: 60%